Information technology for schools : (Jossey-Bass, 2001)
This unique book leads to higher levels of student performance by providing a thoughtful context and practical framework for understanding the potential of technology to enrich teaching and learning. From the classroom to the school district, Information Technology for Schools presents successful approaches to using technology to serve different educational priorities. The contributing authors discuss the challenge of planning integrated information systems, establishing benchmarks to measure overall progress, and harnessing technology to improve curriculum and teaching practice. They highlight practical questions for educational stakeholders and provide sound advice on building effective information technology systems.